Recall of Point-of-Sale Marketing Predicts Cigar and E-Cigarette Use Among Texas Youth. Issue 8 (23rd October 2017) - Pasch, Keryn E; Nicksic, Nicole E; Opara, Samuel C; Jackson, Christian; Harrell, Melissa B; Perry, Cheryl L
Abstract: Introduction: While research has documented associations between recall of point-of-sale (POS) tobacco marketing and youth tobacco use, much of the research is cross-sectional and focused on cigarettes. The present longitudinal study examined recall of tobacco marketing at the POS and multiple types of tobacco use 6 months later. Methods: The Texas Adolescent Tobacco Advertising and Marketing Surveillance System (TATAMS) is a large-scale, representative study of 6th, 8th, and 10th graders in 79 middle and high schools in five counties in Texas. Weighted logistic regression examined associations between recall of tobacco advertisements and products on display at baseline and ever use, current use, and susceptibility to use for cigarette, e-cigarette, cigar, and smokeless products 6 months later. Results: Students' recall of signs marketing e-cigarettes at baseline predicted ever e-cigarette use and increased susceptibility to use e-cigarettes at follow-up, across all store types. Recall of e-cigarette displays only predicted susceptibility to use e-cigarettes at follow-up, across all store types. Both recall of signs marketing cigars and cigar product displays predicted current and ever cigar smoking and increased susceptibility to smoking cigars at follow-up, across all store types. Recall of cigarette and smokeless product marketing and displays was not associated with tobacco use measures. Conclusion: The POS environment continues to be an important influence on youth tobacco use. Restrictions on POS marketing, particularly around schools, are warranted. Implications: Cross-sectional studies have shown that exposure to POS cigarette marketing is associated with use of cigarettes among youth, though longitudinal evidence of the same is sparse and mixed. Cross-sectional studies have found that recall of cigars, smokeless product, and e-cigarette tobacco marketing at POS is associated with curiosity about tobacco use or intentions to use tobacco among youth, but limited longitudinal research has been conducted. Findings from the present longitudinal study suggest that recall of tobacco marketing at retail POS predicts ever use of e-cigarettes and cigars, current use of cigars, and susceptibility to cigar and e-cigarette use among youth.